1976
DOI: 10.3367/ufnr.0119.197607f.0541
|View full text |Cite
|
Sign up to set email alerts
|

Second law of thermodynamics and thermally excited quantum oscillators

Abstract: Появление газодинамического лазера, первого действующего прибора, который использует принцип квантовой генерации электромагнитных колебаний и непосредственно преобразует тепловую энергию в когерент-ное излучение, возродило интерес к взаимосвязи между развивающейся квантовой электроникой и термодинамикой, наукой с хорошо устояв-шимися положениями. При ознакомлении с историей оказалось, что идея непосредственного преобразования тепла в когерентное излучение •с помощью квантовых генераторов была высказана довольн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…͑82͒ can be negative, e.g., for T h = T c , which means that the work is put into the system. 8 An example of such a behavior is given by a harmonic oscillator with frequency , where n = បn, and the specific heat is…”
Section: Third Level Maximization Strategymentioning
confidence: 99%
“…͑82͒ can be negative, e.g., for T h = T c , which means that the work is put into the system. 8 An example of such a behavior is given by a harmonic oscillator with frequency , where n = បn, and the specific heat is…”
Section: Third Level Maximization Strategymentioning
confidence: 99%
“…The nearsurface layer is determined by the average thermal speed of these atoms and the lifetime of the excited lowest level of the 4f Nÿ1 5d6s 2 configuration. (iii) Contrary to the conclusions made in [4], a cooler is not required for the process of thermal creation of population inversion (cooler acts only as a condenser, preventing evaporated atoms from returning to metal surface). The population inversion takes place in the two level system.…”
mentioning
confidence: 47%
“…The analysis of the above-listed methods for direct heat conversion into electromagnetic radiation in Ref. [4] showed that quantum generators with thermal excitation comply with the second law of thermodynamics and it is necessary to use both a heater and a cooler (heat machine) for their operation. For example, the population inversion in ruby sample appears during temperature leveling [2].…”
mentioning
confidence: 99%
“…Effectively large temperatures arise naturally in biomolecular systems due to the stored energy, which-when recalculated in terms of temperature-is some 20-50 times larger than the room temperature [31]. The model (1,5) was introduced and studied in the quantum setting [6][7][8][9][10], as a model for maser. Closely related models were studied recently in the context of photovoltaic engines [15].…”
mentioning
confidence: 99%
“…the machine does not function as a heat-engine; cf. (7). Thus the coupling between structure and function, which is encoded in P (E 1 , E 2 , E 3 ) must be informative.…”
mentioning
confidence: 99%